1979
DOI: 10.1021/j100477a008
|View full text |Cite
|
Sign up to set email alerts
|

Ionic diffusion and ion clustering in a perfluorosulfonate ion-exchange membrane

Abstract: Tracer self-diffusion coefficients for Na+ and Cs+ have been measured in Nation perfluorosulfonate ion-exchange membranes for three solvent systems: water, methanol, and acetonitrile. Results indicate that ion clustering exerts a pronounced effect on the diffusional properties of this material. Diffusion coefficients and activation energies of diffusion vary dramatically for small changes in swelling. This is attributed to changes in the ability of counterions to move between clusters. The ionic transport prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 1 publication
1
62
0
Order By: Relevance
“…From experimental testing it is seen that this prediction counters the physical data that have been measured for the IPT. To address this discrepancy, the results of Yeager et al 41,42 were used to incorporate the temperature dependent variations in the diffusion coefficient d. These results demonstrated that the changes in d outweighed those of T, causing the high frequency impedance of the model to decrease with temperature, a result that agrees with experimental studies. The series of experimental studies conducted in this research also support and validate the proposed model.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…From experimental testing it is seen that this prediction counters the physical data that have been measured for the IPT. To address this discrepancy, the results of Yeager et al 41,42 were used to incorporate the temperature dependent variations in the diffusion coefficient d. These results demonstrated that the changes in d outweighed those of T, causing the high frequency impedance of the model to decrease with temperature, a result that agrees with experimental studies. The series of experimental studies conducted in this research also support and validate the proposed model.…”
Section: Discussionmentioning
confidence: 63%
“…In the temperature study, parameters in the impedance model were tuned to the room temperature response. Then, temperature values were tuned in accordance with experimental conditions and the diffusion coefficient was scaled through previously published results of Yeager et al 41,42 These terms were then applied to the model to predict the response at temperatures above and below the room temperature base line. These results, coupled with those of the diluent and pretension studies, indicate very good correlations between the predicted response and measured data, while also supporting the overall validity of this electrical impedance model of the ionic polymer transducer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[35][36][37][38][39][40] Finally, an average coverage along the channel can be obtained by integration of the local coverage along the length of the channel, 0 < ξ < 1:…”
Section: Modelmentioning
confidence: 99%